Maternal Methyl-Donor Micronutrient Supplementation During Pregnancy Promotes Skeletal Muscle Differentiation and Maturity in Newborn and Weaning Pigs - He, Qin; Zou, Tiande; Chen, Jun; Jian, Li; He, Jia; Xia, Yingying; Xie, Fei; Wang, Zirui; You, Jinming (Frontiers in Nutrition, 2020)
Abstract Adequate maternal methyl-donor micronutrients (MET) intake are important determinants of the organ development and metabolic renovate of offspring. The mechanism involved in skeletal myogenesis and the effect of MET supplementation during pregnancy on the maternal body remains unclear. Thus, this study aimed to investigate the potential effect of methyl donor micronutrients (MET) on skeletal muscle development and metabolism in offspring using pig models. Forty-three Duroc × Erhualian gilts were assigned to two dietary groups during gestation: control diet (CON) and CON diet supplemented with MET (folic acid, methionine, choline, vitamin B6 and vitamin B12). The results showed that maternal MET exposure during pregnancy significantly increased the concentration of protein, triiodothyronine (T3) and thyroxine (T4) in colostrum and methyl metabolites, including S-adenosylmethionine (SAM), S-adenosyl-L-homocysteine (SAH), 5-methyl-tetrahydrofolate (5-MTHF) and betaine, in the maternal and offspring umbilical vein serum. A similar pattern was demonstrated in the body weight gain and myofiber diameters in offspring. In addition, maternal MET supplementation significantly increased the concentration of offspring serum insulin-like growth factor 1 (IGF-1), T3 and T4, up-regulated the mRNA expression of IGF-1 and IGF-1 receptor (IGF-1r) and the phosphorylation level of protein kinases in offspring longissimus dorsi muscle and up-regulated the expression of myogenic genes and fast myosin heavy chain (fast MyHC ) in offspring skeletal muscle. Supplementing sows with higher levels of MET during gestation may promote skeletal muscle differentiation and maturity and improve the skeletal muscle mass of the piglets.